The Substitution Effect of Avocado Seed Flour on The Organoleptic Properties of Sponge Cake - Sarah Megarani; Mia Srimiati (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2018)
The aims of this study was to determine the substitution effect of avocado seed flour on the organoleptic properties of sponge cake. Method: This was experimental study where the substitution rate of wheat flour with avocado seeds was treated. There were 3 treatments, F1 (15% of avocado seed flour), F2 (25% of avocado seed flour), F3 (40% of avocado seed flour) and F0 (control). The substitution of avocado seed flour had a significant effect (P 0.05) on the organoleptic properties. The F1 (15%) was the best formula with the highest acceptability compared to other formulas determined by hedonic test. The characteristics of the sponge cake were sweet taste, very fragrant aroma, very soft texture, and have a yellow colour. The product contained 44.77% (w/w) of carbohydrates, 17.97% (w/w) fat, 8.04% (w/w) protein, 28.02% (w/w) water, and 1.2% (w/w) ash. To get the best acceptability of the sponge cake, the maximum substitution of avocado seed flour in the sponge cake is 15%.